Liquid chromatography-high resolution mass spectrometry based analysis of persistent mobile organic compounds in aqueous samples: Method development and optimization - Kyriaki Anagnostopoulou; Vasileios Alampanos; Eleni Evgenidou; Dimitra A. Lambropoulou (Green Analytical Chemistry)
Persistent Mobile Organic Compounds (PMOCs) represent a critical threat to water resources due to their high solubility, resistance to degradation, and potential toxicity, posing risks to human health and ecosystems. Their detection and analysis are particularly challenging, necessitating advanced analytical techniques to support regulatory measures and ensure safe drinking water. This study addresses these challenges by developing and optimizing a robust method for PMOC detection, integrating solid-phase extraction with liquid chromatography-high resolution mass spectrometry (SPE-LC-HRMS). By bridging analytical gaps in PMOC identification, the research contributes to water quality protection and aligns with global environmental and public health goals. The method is designed to accommodate the diverse physicochemical properties of PMOCs, enabling the detection of a broad spectrum of compounds. Innovations include the creation of a comprehensive PMOC target list, optimization of sample preparation with specialized SPE cartridges, and the fine-tuning of chromatographic and HRMS parameters. A central composite design and desirability function (DF) approach were used to optimize the HRMS analysis, while the most suitable SPE cartridge, column, and mobile phase composition were carefully selected through experimental trials. The method achieved recoveries within 70–120 % and excellent linearity (r² > 0.997) for all analytes. Validated under European directives (2002/657/EC and SANTE 11,813/2017), the study offers a sensitive, reliable, and regulatory-compliant framework for PMOC monitoring in water systems. By addressing both scientific and regulatory demands, this work advances environmental analytical chemistry and strengthens efforts to protect water resources from emerging contaminants.